Laboratory screening for erythropoietin abuse in sport: an emerging challenge - Lippi, G.; Guidi, G. (Clinical Chemistry and Laboratory Medicine, 2000)
The growing diffusion of banned practice to improve the athletic performances is forcing clinical laboratories to identify and standardize reliable assays to detect potential unfairness. Among the doping practices, the use of recombinant human erythropoietin is becoming fairly popular, due to simplicity and safeties of administration and troublesome detection. The heterogeneous response rate, the presence of a little but significant amount of naturally occurring hormone, the short half-life exhibited by recombinant human erythropoietin and the lack of standardization of commercial assays appear the main problems to overcome. Aim of the present article is to provide a critical review of some of the more widespread laboratory techniques currently available for the screening for erythropoietin abuse in sport.